STUDI GANGGUAN TRANSFORMATOR DISTRIBUSI PADA JARINGAN DISTRIBUSI 20 KV DI PT PLN (PERSERO) RAYON NATAR - Khalifah K, Siti; Anasta, Nambi (ITP Press, 2025)
The use of distribution transformers has a very important role in the distribution of electrical energy in a distribution system. The transformer used must be maintained properly so that its reliability is maintained stable, so as to avoid the form of interference. If a disturbance occurs, it will result in a break in the continuity of electricity distribution to consumers and also losses for consumers and PLN itself. Some disturbances that often occur are due to overloads, unbalanced loads, lightning strikes and internal disturbances in the transformer (disturbances originating from the transformer itself). Through this research, a case study will be taken on the 20 kV distribution network at PT PLN (Persero) Rayon Natar. Keywords : Distribution System, Transformer, PLN, Rayon Natar